Implementasi Layanan Firebase pada Pengembangan Aplikasi Sewa Sarana Olahraga Berbasis Android - Kurniawan, Teguh; Samsudin, Samsudin; Triase, Triase (Teknik Informatika Universitas Pamulang, 2021)
One of the business sectors that rarely gets digital innovation is the sports business sector, such as the sports field rental business. The problem in this business is that there are still many business actors and their customers who carry out the conventional reservation process, namely by making books manually and this has an impact on the customer experience when conducting leasing transactions, and for business actors it also has an impact on financial recapitulation due to incorrect calculations. The purpose of this research is to develop an Android-based application that is able to provide a much faster and easier sports rental transaction process by integrating with firebase services (firebase authentication, firebase realtime database, firebase cloud messaging). This study uses the method of developing the Rapid Application Development system and in collecting data using qualitative methods, namely observation, interviews, and literature study. From this research, an android-based application has been successfully developed that is able to solve the problem of conventional sports facilities rental and minimize the occurrence of calculation errors in financial recapitulation by integrating it with firebase services.